Conducta obstétrica en multípara de 38 años de edad con 39.5 semanas de gestación + óbito fetal. - Ramírez Anchundia, Xavier Alexander (2021)
The present clinical case on stillbirth aims to expose the obstetric behavior in multiparous women of 38 years of age with 39.5 weeks of gestation plus stillbirth, this case study focused on intrauterine fetal death as a health problem identified in indigenous communities far from the city of Guaranda, who, due to their ancestors, take traditional measures to control and monitor many pathologies, particularly those in pregnancy. The methodology applied for the case was obstetric diagnosis by applying Leopold's maneuvers to determine fetal statics and determine the focus of auscultation, as there were no results, Obstetric ultrasound was used, finding a single male intrauterine product with an approximate weight of 3,000 gr and absence of fetal heart rate, at the local physical examination the bishop test was 10 points, so the patient was admitted to conduct labor, which lasted 4 hours during which antibiotics were administered therapy for the risk of infection.